Cannabis use and transition to psychosis in people at ultra-high risk. Issue 12 (6th February 2014) - Valmaggia, L. R.; Day, F. L.; Jones, C.; Bissoli, S.; Pugh, C.; Hall, D.; Bhattacharyya, S.; Howes, O.; Stone, J.; Fusar-Poli, P.; Byrne, M.; McGuire, P. K.
Abstract : Background: Cannabis use is associated with an increased risk of developing a psychotic disorder but the temporal relationship between cannabis use and onset of illness is unclear. The objective of this study was to assess prospectively the influence of cannabis use on transition to psychosis in people at ultra-high risk (UHR) for the disorder. Method: Lifetime and continued cannabis use was assessed in a consecutively ascertained sample of 182 people (104 male, 78 female) at UHR for psychosis. Individuals were then followed clinically for 2 years to determine their clinical outcomes. Results: Lifetime cannabis use was reported by 134 individuals (73.6%). However, most of these individuals had stopped using cannabis before clinical presentation ( n = 98, 73.1%), usually because of adverse effects. Among lifetime users, frequent use, early-onset use and continued use after presentation were all associated with an increase in transition to psychosis. Transition to psychosis was highest among those who started using cannabis before the age of 15 years and went on to use frequently (frequent early-onset use: 25%; infrequent or late-onset use: 5%; χ 2 1 = 10.971, p = 0.001). However, within the whole sample, cannabis users were no more likely to develop psychosis than those who had never used cannabis (cannabis use: 12.7%; no use: 18.8%; χ 2 1 = 1.061, p = 0.303). Conclusions: In people at UHR for psychosis, lifetime cannabis use was common but not related to outcome. Among cannabis users, frequent use, early-onset use and continued use after clinical presentation were associated with transition to psychosis.